PERFORMANCE IMPROVEMENT MODEL WITH STRATEGY ORIENTATION MIX AND MARKETING MIX BASED ON THE USE OF INFORMATION TECHNOLOGY FOR SMALL BUSINESS BATIK CENTRAL JAVA - Darmanto Darmanto; Basuki Sri Rahayu; Kasidin Kasidin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to produce a model for improving the performance of batik small businesses based on the use of information technology. The preparation of this model starts from proving the influence of the strategic orientation mix and marketing mix on the performance of Batik small businesses. The strategic orientation mix consists of organizational change capability, innovation orientation, competitive advantage and market orientation strategy. Market orientation strategy consists of customer and competitor orientation strategies. The marketing mix consists of product, price, distribution, promotion. The effect of this variable is determined by the use of information technology. Information technology consists of social media, e-commerce and information systems The research population is Batik small business in Central Java. A sample of 100 was selected by convenience sampling technique, Structural Equation Model (SEM) analysis was used to examine the effect of independent variables on the performance of small batik businesses, the role of the use of information technology in moderating the strategic orientation mix and marketing mix on the performance of batik small businesses. This model proves that the strategic orientation variable and the marketing mix have a significant positive effect on the performance of small batik businesses by being moderated by the use of information technology. Keywords: Model, Performance; Batik; Use of information technology, Small business